Faktor-Faktor Yang Berhubungan Dengan Pemenuhan Kebutuhan Spiritual Care Pasien Yang dirawat di Rumah Sakit Awal Bros Batam - Siti Khotijah; Utari Christya Wardhani; Umi Eliawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One aspect of professional service in bathing is providing spiritual care for problems. This is important because when a person's physical condition is disturbed, there is a possibility of experiencing emotional changes. In these conditions, a person's spiritual aspect is needed to overcome these emotional changes, but in reality the patient's spiritual care needs are not paid enough attention to by nurses. This study aims to determine the factors related to meeting the spiritual care needs of patients treated at Awal Bros Hospital Batam. The research was conducted in August 2023. This research is a quantitative study with a cross sectional research design. The sample in the study amounted to 55 respondents with a sampling technique that is total sampling. The research data was processed using the Chi Square statistical test. The results of the bivariate analysis showed that there was a significant relationship between the knowledge and motivation of nurses and the provision of spiritual care needs of patients treated at Awal Bros Hospital Batam with a p-value for knowledge of 0.004 (?<0.05) and for motivation with a p-value value 0.009 (?<0.05). The researcher hopes that this research can be used as reference material for hospitals to know the importance of the knowledge and motivation of nurses to meet the spiritual care needs of patients at Awal Bros Batam Hospital, so that this research can be used as a basis for strategies to increase the role of nurses as one of the foundations needed. hospitals in the process of providing health services, especially in terms of patient care is increasing.